2014
DOI: 10.1099/mic.0.081042-0
|View full text |Cite
|
Sign up to set email alerts
|

Interaction of the carbon monoxide-releasing molecule Ru(CO)3Cl(glycinate) (CORM-3) with Salmonella enterica serovar Typhimurium: in situ measurements of carbon monoxide binding by integrating cavity dual-beam spectrophotometry

Abstract: Carbon monoxide (CO) is a toxic gas that binds to haems, but also plays critical signalling and cytoprotective roles in mammalian systems; despite problems associated with systemic delivery by inhalation of the gas, it may be employed therapeutically. CO delivered to cells and tissues by CO-releasing molecules (CO-RMs) has beneficial and toxic effects not mimicked by CO gas; CO-RMs are also attractive candidates as novel antimicrobial agents. Salmonella enterica serovar Typhimurium is an enteropathogen causing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 40 publications
0
16
0
Order By: Relevance
“…Furthermore, intestinal infections are an important factor in the development of IBD ( 51 ) and most of the evidence available to date supports the notion that HMOX1 promotes bacterial clearance, diminishing intestinal inflammation ( 90 ). Moreover, it has been demonstrated that CO can interact directly with heme groups of the bacterial electron transport chain, suggesting that HMOX1 has an effect in bacterial infections not only through the modulation of the immune response, but by the direct interaction with the pathogen ( 119 ). In another field, HMOX1 has also been associated with colorectal cancer, being suggested as a novel target for cancer therapy ( 106 ).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, intestinal infections are an important factor in the development of IBD ( 51 ) and most of the evidence available to date supports the notion that HMOX1 promotes bacterial clearance, diminishing intestinal inflammation ( 90 ). Moreover, it has been demonstrated that CO can interact directly with heme groups of the bacterial electron transport chain, suggesting that HMOX1 has an effect in bacterial infections not only through the modulation of the immune response, but by the direct interaction with the pathogen ( 119 ). In another field, HMOX1 has also been associated with colorectal cancer, being suggested as a novel target for cancer therapy ( 106 ).…”
Section: Discussionmentioning
confidence: 99%
“…That study further demonstrated that HMOX1‐derived CO induces bactericidal activity in mouse macrophages to protect them from Salmonella infection. However CO can directly inhibit the respiration of Salmonella and kill it in a concentration dependent manner . In contrast with the above‐cited studies, Mitterstiller et al, demonstrated reduced survival of Salmonella upon pharmacological inhibition of HMOX1 or upon its silencing.…”
Section: Bacterial Infectionsmentioning
confidence: 91%
“…314315 CORM3 was also shown to have antibacterial activity against E. coli , 313,318 and S. typhimurium after bacterial uptake of the drug. 316 Both CORM2 and CORM3 exerted antibacterial activity against antibiotic-resistant strains of H. pylori . 319 Recent advances using PhotoCORMs demonstrate photoactivatable toxicity of these compounds toward E. coli bacteria.…”
Section: Therapeutic Stategies Involving Application Of Ho-1 End Prodmentioning
confidence: 99%